Modern human teeth unearthed from below the ∼128, 000-year-old level at Punung, Java: A case highlighting the problem of recent intrusion in cave sediments. Issue 163 (February 2022) - Kaifu, Yousuke; Kurniawan, Iwan; Yurnaldi, Dida; Setiawan, Ruly; Setiyabudi, Erick; Insani, Halmi; Takai, Masanaru; Nishioka, Yuichiro; Takahashi, Akio; Aziz, Fachroel; Yoneda, Minoru
Abstract: The emergence of modern humans in the eastern edge of the Eurasian Continent is debated between two major models: early (∼130−70 ka) and late (∼50 ka) dispersal models. The former view is grounded mainly on the claims that several cave sites in Southeast Asia and southern China yielded modern human fossils of those early ages, but such reports have been disputed for the lack of direct dating of the human remains and insufficient documentation of stratigraphy and taphonomy. By tracing possible burial process and conducting direct dating for an early Late Pleistocene paleontological site of Punung III, East Java, we here report a case that demonstrates how unexpected intrusion of recent human remains into older stratigraphic levels could occur in cave sediments. This further highlights the need of direct dating and taphonomic assessment before accepting either model. We also emphasize that the state of fossilization of bones and teeth is a useful guide for initial screening of recent intrusion and should be reported particularly when direct dating is unavailable. Additionally, we provide a revised stratigraphy and faunal list of Punung III, a key site that defines the tropical rainforest Punung Fauna during the early Late Pleistocene of the region.